7.6k views
2 votes
What is the inverse of the function h(x) =3/2(x-11)

User Jakstack
by
4.9k points

2 Answers

3 votes

Answer:


h^(-1)(x) =
(2)/(3) x + 11

Explanation:

let y = h(x) and rearrange making x the subject , that is

y =
(3)/(2) (x - 11 ) ← multiply both sides by 2 to clear the fraction

2y = 3(x - 11) ← distribute

2y = 3x - 33 ( add 33 to both sides )

2y + 33 = 3x ( divide all terms by 3 )


(2)/(3) y + 11 = x

Change y back into terms of x with x =
h^(-1)(x) , thus


h^(-1)(x) =
(2)/(3) x + 11

User Frow
by
5.1k points
2 votes

Answer:

Explanation:

What is the inverse of the function h(x) =3/2(x-11)-example-1
User Deshtop
by
5.2k points